1977
DOI: 10.1111/j.1365-2389.1977.tb02261.x
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Pore Sizes in Fine‐textured Soils: A Review of Existing Techniques

Abstract: Pore size distributions obtained from the relationship between moisture content and suction are not dependable in fine-textured soils because of shrinkage. To overcome this problem, methods such as nitrogen sorption, mercury intrusion porosimetry, nonpolar liquid desorption and thin sectioning have been used. In order to predry samples without changes in the pore system, freeze-drying, organic liquid replacement of soil water, and critical point drying techniques have been employed. These methods of soil dryin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0
6

Year Published

1980
1980
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(47 citation statements)
references
References 38 publications
0
38
0
6
Order By: Relevance
“…We converted the structural pores water retention curves into the structural pore size distributions of equivalent cylindrical pores using the Jurin-Laplace equation (e.g. Lawrence, 1977). Since only the structural pores allow air entry in the tensiometer reading pressure range, we did not apply the procedure to the plasma pores.…”
Section: Structural Pore Size Distributionmentioning
confidence: 99%
“…We converted the structural pores water retention curves into the structural pore size distributions of equivalent cylindrical pores using the Jurin-Laplace equation (e.g. Lawrence, 1977). Since only the structural pores allow air entry in the tensiometer reading pressure range, we did not apply the procedure to the plasma pores.…”
Section: Structural Pore Size Distributionmentioning
confidence: 99%
“…Intensive tillage may result in deterioration of soil structure and eventually a decrease in crop yield (Cotching et al, 1979;Chan, 1982;Pagliai et al, 1995), because of changes in porosity and pore size distribution (Lawrence, 1977;Ringrose-Voase and Bullock, 1984). Comparative effect of tillage methods on pore size distribution has been reported for some soils in Italy (Pagliai et al, 1983(Pagliai et al, , 1984(Pagliai et al, , 1995, New Zealand (Francis et al, 1987;Hermavan and Cameron, 1993), Australia (Chan, 1982), Canada (Shipitalo and Protz, 1987;Azooz et al, 1996), Japan (Naohiro et al, 1994) and USA (Mahboubi et al, 1993;Lal et al, 1994).…”
Section: Introductionmentioning
confidence: 96%
“…Quantitative information about the amount, size, configuration or distribution of the pore space is more important in characterizing the soil as a medium for plant growth than particle size distribution (Danielson and Sutherland, 1986). Soil structure is defined in terms of its functional attributes comprising soil porosity and pore size distribution (Lawrence, 1977;Greenland, 1977). Ringrose-Voase and Bullock (1984) and Pagliai et al (1984) reported that porosity and pore size distribution were the best indicators of soil structure, because the size, shape and continuity of pores affect important soil processes.…”
Section: Introductionmentioning
confidence: 99%
“…Although not revealing the morphology of the pores, indirect observation methods cover the whole range of pore sizes. They include mercury intrusion porosimetry, non-polar liquid desorption and water desorption (Lawrence, 1977), as well as the measurement and modelling of shrinkage curves. This latter method is of growing interest for the characterization of soil pore space and structure.…”
Section: Introductionmentioning
confidence: 99%